Pest Management in the Postharvest Agricultural Supply Chain Under Climate Change - Gerken, Alison R.; Morrison, William R. (Frontiers in Agronomy, 2022)
Climate change is a danger to the agricultural system and will impact the availability of food to feed the world. While much attention has focused on the effects of climate change on pest management prior to harvest, much less attention and time has been devoted to determining the effects of climate change on pest management in the postharvest supply chain from farm to fork. Climate change may percolate to pest management at a macro level through compositional changes in which species attack commodities through distributional changes or what commodities are grown in a region (and thus processed in that area). However, climate change may also result in altered microclimates at food facilities, which can be tied to increased generation times, elevated damage and contamination potential, greater abundance of species, and greater need for external inputs. A variety of integrated pest management (IPM) strategies may help increase the resiliency and adaptation of management to climate change. Tactics susceptible to warming temperature changes in climate showing decreased efficacy include semiochemical-based, behaviorally-based tactics, a subset of insecticides (e.g., pyrethrins and pyrethroids), and those that rely on low temperature (e.g., grain aeration, grain chilling). Tactics at food facilities showing resilience to warming temperature changes in climate include packaging, other groups of insecticides, and likely sanitation. Data gaps include predicting changing distributions for stored product insects under climate change, translating macro climate changes into microclimate changes at food facilities, and rigorously investigating how IPM tactic efficacy varies under changing climate. Increased scrutiny of how climate change will affect pest management in the postharvest supply chain will deliver improved outcomes for the entire agricultural system.